Features of TV and Radio Internet Broadcasting in Armenia - AVETISYAN, ARMEN (Bulletin of Yerevan University B: Philology, 2021)
The process of penetration of traditional media of various types into the Internet has been uneven. It should be noted that complex technical innovations were required before the emergence of the Internet radio and TV. Radio and television, of course, as well as throughout the world, entered the Internet in Armenia rather late. The research of the Armenian Internet radio stations shows that Internet broadcasting in our country is in the process of establishment up to this day. With the exception of the Public Radio of Armenia, “Radio Liberty” and “The News Radio 106,5 FM”, the others have not yet been able to become competitive in comparison with other types of the Internet media. Unlike radio, television companies made their websites later, but the process of their involvement in the Internet space proved to be quite effective. All of the prestigious TV channels of the country are presented on the Internet through their websites. In addition, there is already a noticeable trend of formation of its independent online content, which will work in the offline mode. Nevertheless, in Armenia, it is still too early to speak about the end of the process of the internetization of the two media giants – radio and television.